(untitled) (Nigerian Journal of Pharmaceutical Research, 2021)
Background: While everyone can be affected by stress, there is evidence to suggest that students might be more prone. Objective: To assess perceived stress levels and well-being among undergraduate pharmacy students’ of Ahmadu Bello University, in addition to identifying common stressors and coping mechanisms used by the students. Methods: A survey was conducted on second to fifth year undergraduate pharmacy students of the institution from August to November 2019. A self-administered questionnaire was used to collect data about the students’ socio-demographic characteristics, stress levels (Perceived Stress Scale-10), well-being (World Health Organization-5 well-being index), stressors and coping strategies. Student t-tests, analysis of variance (ANOVA) and Pearson’s bivariate correlation were used to compare means and correlations between variables. P < 0.05 was considered as statistically significant. Results: Of the 350-questionnaire distributed, 328 were returned producing a 93.7% response rate. Majority of respondents were males (63.1%), and in their third year of study (29.3%). The mean PSS-10 score was 18.4 ± 4.9, and a statistically significant difference in scores were seen across gender (p= 0.001). Over half of the participants (72.8%) also scored 51% or higher on the WHO-5 index. Their most common stressors were volume of course materials 184 (56.1%) and financial constraints 158 (48.2%) respectively. More than half of respondents (64.5%) also sought for emotional support from their families to cope with stress. A statistically significant (p<0.001) negative weak correlation (-0.3) was seen when PSS-10 and WHO-5 scores were compared. Conclusion: Perceived stress levels in female undergraduate pharmacy students were higher than those in their male counterparts, and most of the students had at least good well-being.